World Englishes and linguistic landscapes - Bolton, Kingsley (2015)
The growing intrusion and use of English in the public spaces of the world’s cities alongside national languages and local languages has received increasing attention over the last fifteen years or so. The study of English and other languages in urban public signage has drawn the attention of anthropologists, cultural theorists, and various scholars in sociolinguistics, many of whom have contributed to a body of research on the topic of ‘linguistic landscapes’. Such work is of direct relevance to world Englishes, as the scope of WE is obviously not simply related to the analysis of particular ‘varieties of English’, but much more besides. Today, the linguistic worlds of young people in particular are becoming increasingly diverse, and the linguistic landscapes of individuals are not simply defined through physical space, but also through electronic space, global travel, media awareness and usage, popular culture, as well as the virtual space of the Internet.